CONCENTRATION OF MICROIMPURITIES IN MINERAL CRYSTALS WITH DEFECT LATTICES - Abramovich M.G.; Tauson V.L.; Akimov V.V. (My University, 1989)
Physicochemical equilibria in systems that comprise solid phases with defect crystal lattices are now a major subject of study. The authors describe the quantitative analysis of the degree of concentration of microimpurities in mineral solid solutions with lattice defects of two types typical of natural crystals, namely, low-angle crystal-block boundaries, and zones of interdiffusion of macrocomponents of the solution.